The Influence Of Service Quality On The Level Of Customer Satisfaction Indonesia Sharia Bank - Mega Lestari; Eko Sudarmanto; Alhazar Rinaldi (Institut Agama Islam Sumatera Barat, 2024)
This study aims to determine the effect of service quality on customer satisfaction of Bank Syariah Pariaman City. In this study the authors used quantitative research methods. Data collection techniques using questionnaires, interviews and documentation. The population of this study were Bank Syariah Indonesia customers totaling 1,500 customers and the sample used was 94 customers. The data analysis used is Simple Linear Regression Y = a + bX using the help of SPSS software version 25 for windows. Based on the results of the research analysis conducted t-statistical test which shows that the service quality variable (X) has a positive effect on the customer satisfaction variable (Y) with the results from the coefficient table it is known that the t value is 5.969> t table 0.202 with the significance value of the service variable is 0.00 smaller than 0.05 (0.00 <0.05), thus H₁ is accepted. These results indicate that service quality is one of the variables that affects customer satisfaction. The higher the value of service quality, the stronger the effect on customer satisfaction. Through the coefficient of determination (R²) test, it can be seen that the coefficient of determination (R²) value is 0.279 which indicates that there is a significant influence of the independent or independent variable (service quality) on the dependent or dependent variable ( customer satisfaction) which is 0.279 where the number is rounded up to 28%, and the remaining 72% is influenced by other factors not examined by the researcher.